Effects of Insulin treated Established Diabetes Mellitus (EDM) on the Volume of Placental Parenchyma and Weight of the Neonate (Bangladesh Journal of Anatomy, 2009)
Taking in mind the effects of diabetes mellitus of varying severity on human placenta and their implication on the well being of the fetus, a quantitative study at the macroscopic level was designed. Sixty post caesarean section human placentas were studied of which thirty were from mothers having insulin treated established diabetes mellitus (EDM) considered as EDM group and thirty were from control mother having no diabetes mellitus. The venous plasma glucose level (fasting and two hours after breakfast) of the diabetic mothers in second and third trimester were recorded and the mean of the values were calculated. The value ranged from 5.93 to 10.10 and the mean was 7.28±0.90. The two groups did not differ significantly from each other with age, weight, height, or parity of the mother or in gestational age. Parenchymal volume in control and EDM group were 300.14±75.43 and 309.25±61.64 respectively. The value showed higher mean value in EDM group. The differences did not reach a significant level. The neonatal weight in control and EDM group were 2.95±0.53 and 3.05±0.52 respectively. The neonate did show a tendency towards being heavier in EDM group, but no reached the significant level. There was a significant positive correlation between the neonatal weight and the parenchymal volume in control and EDM groups. Key words: Established Diabetes Mellitus, Placenta, Parenchyma, Neonates.   doi: 10.3329/bja.v7i1.3025 Bangladesh Journal of Anatomy January 2009, Vol. 7 No. 1 pp. 45-48